Performance Analysis of Split-Case Sorting Systems - Johnson, M. Eric; Meller, Russell D. (Manufacturing and Service Operations Management, 2002)
Split-case sorting systems are used in many retail supply chains where items must be distributed in less-than-case quantities, such as orders shipped directly to customers by catalogers and e-tailers or shipments made in less-than-case quantities from a distribution center to a retail store. These systems are particularly effective in order-packing systems where the same item is needed for multiple orders. Items are inducted into a circular sorting conveyor system one unit at a time and then delivered to an order-packing bin designated for a particular customer or retail store. We develop analytical performance models that incorporate the stochastic operating conditions faced by these systems. Our model allows system designers to predict the sorting capacity for different system configurations. More importantly, we use the model to develop insight into the system design and operation.